Pendampingan Kegiatan Tasmi' dalam Penguatan Hafalan Al-Qur'an Santri di Pondok Pesantren Darul Amin Palangka Raya: Pelaksanaan Kegiatan Tasmi' di Pondok Pesantren Darul Amin Palangka Raya, Hasil Pendampingan Kegiatan Tasmi' dalam Penguatan Hafalan Al-Qur'an Santri - nismah saadah cima; Nor Faridatunnisa (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2026)
Tasmi' activities are one form of guidance within the Qur'an memorization (tahfiz) program aimed at helping students maintain and strengthen their memorization. This article aims to describe the implementation and the outcomes of mentoring activities in tasmi' for strengthening students' Qur'an memorization at Darul Amin Islamic Boarding School, Palangka Raya. The community service activity was conducted through the Merdeka Belajar Kampus Merdeka (MBKM) program from February to June 2026. Data were collected through observation, interviews, and documentation during the implementation of the program. The results showed that tasmi' was carried out after students completed the memorization of one juz and was preceded by a memorization reinforcement process through murojaah (review) and repeated recitation. The activity was conducted in the presence of teachers and fellow students using a direct listening system, allowing recitation errors to be corrected immediately. The mentoring activities included coordinating the program, listening to students' memorization, preparing supporting facilities, and documenting the implementation of tasmi'. The activity contributed to increasing the intensity of murojaah, improving memorization readiness, enhancing students' self-confidence, and creating a learning environment that supports the maintenance of Qur'an memorization. Therefore, tasmi' contributes to strengthening students' memorization within the Qur'an tahfiz program.